Is Credit Easing Viable in Emerging and Developing Economies? : An Empirical Approach - Jacome H., Luis I.; Saadi Sedik, Tahsin; Ziegenbein, Alexander (Washington, D.C. : International Monetary Fund, 2018)
During the global financial crisis, many central banks in advanced economies engaged in credit easing. These policies have been perceived as largely successful in reducing stress in financial markets, thus avoiding larger output losses. In this paper, we study empirically whether credit easing is also a viable policy tool to cope with banking crises in emerging and developing economies. We find that credit easing leads to a sharp increase in domestic currency depreciation, high inflation, and a substantial reduction in economic growth in a large panel of emerging and developing economies. For advanced economies, we find the effects to be benign. Our results suggest that emerging and developing economies should be cautious when using credit easing as it may fuel adverse macroeconomic repercussions.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet